Community Security between Cyber Security Challenges and Repercussions and Community Reform Strategies - Al_Obidi, Ansam Faik Abdulrezzak (Tikrit Journal For Political Science, 2023)
The end of the Cold War era between the poles of international powers and competitive displays of conventional arsenals of armaments، including weapons of mass destruction and nuclear weapons، does not mean the return of world peace، the restoration of international security and the cessation of the arms race. All the features of conflicts and wars still exist، but what is radically different is the nature of those wars and conflicts according to the requirements of cyber wars that are silent in their tools and destructive in their effects Stemming from the outputs of technological developments، where the fifth generation and artificial intelligence are two sides of the coin and one، where the comprehensive change in the dynamics of conflict and achievements until the measure of strength depends on the extent of control in the field of electronic spaces and professionalism capable of all its inputs in the midst of a huge amount of risks and cyber digital threats with momentary developments The latest complete coup at all levels، especially with regard to the specificity of societal security and the stability and sovereignty of states، the shift towards the digital world with all its features and developmental features of human life has led to the emergence of challenges commensurate in their risks with the instantaneously developmental nature of the orientation، where cyberspace imposed new challenges and concepts of power، wars، threats and risks that threaten the safety of the individual and the security and sovereignty of the state، which in return necessitated the pursuit of countries to create rehabilitation strategies To achieve its security and national cyber stability In order to be a life path for society as a whole to ward off and deter future cyber risks and wars through cooperation and fruitful interaction between all members of society and supported by the exchange of international experiences and exceptional efforts to supplement cybersecurity by enacting deterrent international laws that determine the risks of future electronic wars.